Human praxis, alternative thinking, and heterogeneous culture – Zygmunt Bauman’s revisionist thought - Brzeziński, Dariusz (Hybris, 2017)
Zygmunt Bauman was one of the leading revisionists in Poland before March 1968. Together with six other academics he was expelled from the University of Warsaw on the basis of the decision of the Minister of Higher Education taken on the 25st March 1968. It should be stressed, however, that at the beginning of his academic career Bauman had been a staunch believer of the Polish United Workers’ Party and an adherent of the Marxist-Leninist ideology. In his first revisionist paper, published soon after the Polish October, he criticized the previous policy of the Party and expressed his hope that significant changes will take place in Poland. As a result of Party withdrawal from the reforms, his attitude towards both the communist rule and Marxism-Leninism had been changing. This paper analyses the evolution of his thought towards revisions. It presents the characteristic features of Bauman’s revisionism as well: an emphasis on human praxis, alternative thinking, and heterogeneity of culture.